Honeycomb catalyst containing spinel type non-noble metal oxide as well as preparation method and application of honeycomb catalyst
By using a combination of fibrous silicate clay support and AB2O4 spinel-type oxide and rare earth minerals, a honeycomb structure catalyst was prepared, which solved the problems of catalyst components agglomeration and insufficient mechanical strength, and achieved the improvement of high catalytic activity and sulfur resistance.
Patent Information
- Application Number
- CN202311302177.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-10-09
AI Technical Summary
In the prior art, spinel-type non-precious metal oxide catalysts are prone to agglomeration of catalyst components during the preparation process, which affects their performance. At the same time, during the molding process, the interface bonding force between the active component and the support is poor, the anti-shrink strength is insufficient, and there is a problem that the active component layering is prone to fall off.
Fibrous silicate clay is used as a support, and is modified by organic acid and mixed with AB2O4 spinel oxide and rare earth minerals containing lanthanum or cerium to form a dry gel-like composite. The honeycomb catalyst is prepared after molding, drying and calcination, which avoids the agglomeration of the catalyst components and improves the mechanical strength and sulfur resistance of the catalyst.
It effectively inhibits the agglomeration of catalyst components, improves catalytic activity and sulfur resistance, enhances the mechanical strength of the catalyst, avoids the problem of easy layering of active components, simplifies the process flow and reduces manufacturing costs.
Smart Images

Figure CN119819285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for degrading volatile organic compounds (VOCs), and in particular to a honeycomb catalyst containing spinel-type non-noble metal oxides, and a preparation method and application thereof. Background Art
[0002] As regulations put forward increasingly stringent standards for the emission of volatile organic compounds (VOCs), VOCs governance has attracted much attention. Catalytic oxidation technology is one of the methods used to degrade VOCs. Catalytic oxidation technology is to completely convert VOCs into CO2 and H2O under the action of a catalyst. It is considered to be the most effective method for VOCs degradation. The catalysts used in catalytic oxidation technology can include precious metal catalysts and non-precious metal catalysts. Precious metal catalysts have the disadvantages of being expensive, scarce in source, easy to be poisoned, and easy to sinter and deactivate at high temperature. Non-precious metal catalysts are mainly composed of transition metal oxides. Non-precious metal catalysts have the advantages of abundant sources and low prices, but they have the disadvantages of low activity and high ignition temperature. Especially when dealing with sulfur-containing organic gases, some non-precious metal catalysts also have the problem of poor sulfur resistance. It has been found that non-precious metal catalysts with spinel structure (AB2O4) have high oxygen mobility, strong redox performance and high stability. This structure can not only effectively improve the catalytic performance of the catalyst and reduce the ignition temperature, but also improve the sulfur resistance of the catalyst.
[0003] CN108889301A provides a spinel-type iron-based catalyst and a method for preparing the same. The A in the iron-based spinel catalyst (AFe2O4) is doped by a sol-gel method, thereby improving the reaction activity and sulfur resistance of the obtained catalyst. However, the preparation of the catalyst involves a step of high-temperature calcination to form a doped spinel-type structure. This will cause a certain degree of agglomeration of the catalyst components, thereby affecting the performance of the catalyst.
[0004] CN112337460A provides a method for preparing a Mn-based spinel phase low-temperature denitration catalyst. The method comprises the steps of: preparing a Mn-based spinel phase catalyst active component by complexing acid solution, rolling and molding with silicon aluminum balls as carriers, and roasting to obtain the Mn-based spinel catalyst. The method also comprises high-temperature roasting, which causes the catalyst components to agglomerate.
[0005] Therefore, how to effectively inhibit the agglomeration of catalyst components in a catalyst containing spinel-type non-noble metal oxides is one of the technical problems that need to be solved in the art.
[0006] In addition, non-precious metal catalysts need to be molded to ensure their mechanical strength. The molding is usually carried out by coating the active component on a honeycomb carrier (such as cordierite) and then calcining to obtain a monolithic catalyst. The obtained monolithic catalyst may have problems such as poor interface bonding between the catalyst active component and the honeycomb carrier, poor anti-scouring strength, and even shedding of the active component coating during use. Summary of the invention
[0007] In order to solve one or more of the problems existing in the above-mentioned prior art, the present invention provides a honeycomb catalyst containing spinel-type non-precious metal oxides. The honeycomb catalyst of the present invention avoids or alleviates the agglomeration of catalyst components, thereby improving the catalytic activity of the honeycomb catalyst. In addition, the honeycomb catalyst of the present invention has excellent sulfur resistance and compressive strength. Moreover, the honeycomb catalyst of the present invention does not have a coated active component layer, avoiding the problem of easy shedding of the active component layer. The present invention also relates to a preparation method and application of the honeycomb catalyst.
[0008] In one aspect, the present invention provides a honeycomb catalyst containing spinel-type non-precious metal oxides, which contains (1) fibrous silicate clay, (2) AB2O4 spinel-type oxide, and (3) rare earth minerals containing lanthanum or cerium, wherein the fibrous silicate clay includes at least one of attapulgite, halloysite, wollastonite or sepiolite, wherein A and B are different non-precious metals and each is selected from at least one of nickel, cobalt, iron, manganese, titanium or copper, and wherein the rare earth mineral containing lanthanum or cerium includes at least one of monazite, lanthanum zinc phosphate or fluorocarbon cerium ore.
[0009] In one aspect, the present invention provides a method for preparing the above honeycomb catalyst, which comprises the steps of:
[0010] (1) providing fibrous silicate clay modified with an organic acid;
[0011] (2) mixing an organic acid-modified fibrous silicate clay, water, a water-soluble salt of A, and a water-soluble salt of B, and drying the mixture to obtain a xerogel-like composite;
[0012] (3) The dry gel-like composite of step (2), the rare earth mineral containing lanthanum or cerium and the extrusion aid are mixed, and the mixture is molded, dried and calcined to obtain the honeycomb catalyst.
[0013] In one aspect, the present invention relates to the use of the honeycomb catalyst in degrading volatile organic compounds.
[0014] Compared with the prior art, the present invention has the following advantages:
[0015] (1) The fibrous silicate clay is modified with an organic acid, and the organic acid is solidified on the surface of the fibrous silicate clay. The solidified organic acid can act as a complexing agent, which helps to adsorb and deposit non-precious metal ions from water-soluble salts on the fibrous silicate clay, and uniformly form particles of the catalyst component containing non-precious metals in situ to prevent them from agglomerating.
[0016] (2) The dry gel-like composite is a composite of an AB2O4 spinel precursor and a fibrous silicate clay. It is mixed, molded and calcined with a rare earth mineral containing lanthanum or cerium to prepare a honeycomb catalyst. This operation helps to effectively dope the rare earth elements into the AB2O4 spinel oxide during the formation of the honeycomb catalyst, thereby greatly increasing the active oxygen vacancies of the catalyst. In addition, both the AB2O4 spinel oxide and the rare earth mineral containing lanthanum or cerium have certain catalytic properties and sulfur resistance. The combination of the two can produce a synergistic effect, thereby giving the final prepared honeycomb catalyst more excellent catalytic performance and sulfur resistance.
[0017] (3) Fibrous silicate clay is used as a carrier to support other catalyst components, such as AB2O4 spinel oxide. Fibrous silicate clay has excellent reinforcing, toughening and bonding functions, thereby improving the mechanical strength of the honeycomb catalyst.
[0018] (4) The preparation method of the present invention does not require the step of coating the active component layer used in the traditional method, which simplifies the process flow, shortens the production cycle, and reduces the manufacturing cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A photo showing the honeycomb catalyst (28 mm in diameter, 14 mm in height) of Example 4;
[0020] Figure 2 is the XRD spectrum of the dry gel composite in Example 4;
[0021] Figure 3 is the XRD spectrum of the dry gel-like composite in Comparative Example 4;
[0022] Figure 4 is the XRD spectrum of attapulgite;
[0023] Figure 5 is a TEM photograph of the dry gel composite in Example 4;
[0024] Figure 6 This is a TEM photograph of the dry gel-like composite in Comparative Example 1. DETAILED DESCRIPTION
[0025] In this document, unless otherwise expressly stated, all percentages and contents are based on mass.
[0026] Except in the examples, all numerical values of parameters herein are to be understood as being modified in all instances by the term "about", whether or not "about" actually appears before the numerical value.
[0027] In one aspect, the present invention provides a honeycomb catalyst containing spinel-type non-precious metal oxides, which contains (1) fibrous silicate clay, (2) AB2O4 spinel-type oxide, and (3) rare earth minerals containing lanthanum or cerium, wherein the fibrous silicate clay includes at least one of attapulgite, halloysite, wollastonite or sepiolite, wherein A and B are different non-precious metals and each is selected from at least one of nickel, cobalt, iron, manganese, titanium or copper, and wherein the rare earth mineral containing lanthanum or cerium includes at least one of monazite, lanthanum zinc phosphate or fluorocarbon cerium ore.
[0028] In this context, "fibrous" refers to a shape in which the length is much greater than the diameter. In one embodiment, the fibrous silicate clay has a diameter of 20-40 nm and a length of 0.5-5.0 μm.
[0029] In one embodiment, the mass ratio of AB2O4 spinel oxide to fibrous silicate clay is 0.08-0.30:1, and the mass ratio of the total amount of AB2O4 spinel oxide and fibrous silicate clay to the lanthanum or cerium-containing rare earth mineral is 0.5-2.0:1.
[0030] Preferably, the honeycomb catalyst is substantially composed of or consists of the following components: (1) fibrous silicate clay, (2) AB2O4 spinel oxide, and (3) rare earth minerals containing lanthanum or cerium.
[0031] In one aspect, the present invention provides a method for preparing the above honeycomb catalyst, which comprises the steps of:
[0032] (1) providing fibrous silicate clay modified with an organic acid;
[0033] (2) mixing an organic acid-modified fibrous silicate clay, water, a water-soluble salt of A, and a water-soluble salt of B, and drying the mixture to obtain a xerogel-like composite;
[0034] (3) The dry gel-like composite of step (2), the rare earth mineral containing lanthanum or cerium and the extrusion aid are mixed, and the mixture is molded, dried and calcined to obtain the honeycomb catalyst.
[0035] In one embodiment, the step (1) of providing the organic acid-modified fibrous silicate clay comprises the steps of: applying an isocyanate silane coupling agent and an organic acid to the fibrous silicate clay. Preferably, the step of providing the organic acid-modified fibrous silicate clay comprises the steps of: applying an isocyanate silane coupling agent to the fibrous silicate clay, wherein the mass ratio of the isocyanate silane coupling agent to the fibrous silicate clay is 0.05-0.15:1; and applying an organic acid to the fibrous silicate clay, wherein the mass ratio of the organic acid to the fibrous silicate clay is 0.05-0.2:1. Optionally, after applying the organic acid, the organic acid-modified fibrous silicate clay is kept at a temperature of 60°C-80°C for 30-90 minutes.
[0036] In one embodiment, the isocyanate silane coupling agent is at least one of 3-isocyanate propyl trimethoxy silane and 3-isocyanate propyl triethoxy silane. The organic acid is one of citric acid and tartaric acid.
[0037] In one embodiment, the mixing of organic acid-modified fibrous silicate clay, water, water-soluble salt of A and water-soluble salt of B in step (2) comprises the steps of: dispersing organic acid-modified fibrous silicate clay in water, wherein the mass ratio of organic acid-modified fibrous silicate clay to water is 0.05-0.2:1; and adding water-soluble salt of A and water-soluble salt of B in such an amount that the mass ratio of AB2O4 spinel oxide to fibrous silicate clay in the obtained honeycomb catalyst is 0.08-0.30:1. Subsequently, the mixture is dried to obtain a dry gel-like composite. For example, the mixture can be evaporated to dryness at 85°C-95°C, dried at 110°C-140°C for 1-3 hours, and crushed to obtain a dry gel-like composite. The dry gel-like composite contains AB2O4 spinel oxide precursor and fibrous silicate clay. Specifically, the dry gel-like composite is a composite of AB2O4 spinel oxide precursor and fibrous silicate clay.
[0038] In one embodiment, the water-soluble salt of A is at least one of the nitrate, hydrochloride, sulfate or acetate of A, and the water-soluble salt of B is at least one of the nitrate, hydrochloride, sulfate or acetate of B.
[0039] The present invention has no special restrictions on the extrusion aid, and the commonly used extrusion aids in the art can be used. Examples of extrusion aids include, but are not limited to, one or more of polyols, cellulose, and carbon materials, preferably C2-12 polyols, further preferably ethylene glycol, diethylene glycol, triethylene glycol, glycerol, and further preferably glycerol. In order to achieve good dispersion of the extrusion aid, a polar dispersant can usually be used to dissolve or disperse it. Polar dispersants include, but are not limited to, one or more of water, methanol, ethanol, propanol, butanol, and pentanol. It is preferred to use an aqueous liquid or dispersion of the dispersant. In one variation, an aqueous solution of glycerol with a glycerol mass concentration of 10-100%, preferably 25-100%, is used as an extrusion aid. In one embodiment, the step (3) of mixing the dry gel-like composite, the rare earth mineral containing lanthanum or cerium and the extrusion aid of step (2) includes the steps of: kneading the dry gel-like composite, the rare earth mineral containing lanthanum or cerium and the aqueous solution of glycerol in step (2) for 30-90 minutes, wherein the mass ratio of the dry gel-like composite to the rare earth mineral containing lanthanum or cerium is 0.5-2.0:1 and the mass ratio of glycerol to the dry gel-like composite is 0.05-0.1:1, and the mass percentage concentration of the glycerol aqueous solution is 25-100%; and performing mud kneading 4-6 times. Subsequently, the mixture is molded, dried and calcined to obtain the honeycomb catalyst. For example, the mixture is molded from an extruder, dried at 90°C-120°C for 30-60 minutes and calcined at 550°C-750°C for 2-8 hours to obtain the honeycomb catalyst. In one variation, the extruder has a honeycomb-shaped mold, such as a 28mm diameter honeycomb circular mold. In one variation, the drying is microwave drying at 90°C to 120°C for 30 to 60 minutes.
[0040] In one aspect, the present invention relates to the use of the honeycomb catalyst in degrading volatile organic compounds.
[0041] In one embodiment, the degradation of volatile organic compounds includes: loading the honeycomb catalyst in a reactor, introducing a gas containing volatile organic compounds into the reactor, and heating the reactor at a gas space velocity of 4000-25000 h / min. -1 The reaction is carried out at a temperature of 150-550°C to remove volatile organic matter in the gas.
[0042] Example
[0043] The present invention will be described in detail below by way of examples. The examples are intended to illustrate but not to limit the present invention in any way.
[0044] Example 1
[0045] Under stirring, 0.25 kg of 3-isocyanatepropyltrimethoxysilane was applied to 5.0 kg of fibrous halloysite, and 0.25 kg of citric acid was applied to the halloysite, and the mixture was kept at 80° C. for 30 minutes to obtain citric acid-modified halloysite.
[0046] 1.0 kg of citric acid-modified halloysite was dispersed in 20.0 kg of deionized water, and 0.36 kg of cobalt nitrate and 0.18 kg of nickel nitrate were added and stirred until completely dissolved. The mixture was heated to 85°C to evaporate water, dried at 110°C for 3 hours, and crushed to obtain a dry gel composite containing a precursor of NiCo2O4 spinel and halloysite.
[0047] 1.0 kg of dry gel-like composite, 2.0 kg of lanthanum zinc phosphate and 0.60 kg of glycerol aqueous solution (glycerol mass concentration 25%) were kneaded in a kneader for 30 minutes, and then slurry-kneaded in a vacuum slurry kneader for 4 times. The mixture was extruded from a molding extruder into a honeycomb shape, microwave-dried at 90°C for 60 minutes, and calcined at 550°C for 4 hours to obtain a honeycomb catalyst.
[0048] Example 2
[0049] Under stirring, 0.75 kg of 3-isocyanatepropyltriethoxysilane was applied to 5.0 kg of wollastonite, and 1.0 kg of tartaric acid was applied to the wollastonite, and the mixture was kept at 60°C for 90 minutes to obtain tartaric acid-modified wollastonite.
[0050] 1.0 kg of tartaric acid-modified wollastonite was dispersed in 5.0 kg of deionized water, and 0.067 kg of manganese chloride and 0.036 kg of copper chloride were added and stirred until completely dissolved. The mixture was heated to 95°C to evaporate water, dried at 140°C for 1 hour, and crushed to obtain a dry gel composite containing CuMn2O4 spinel precursor and wollastonite.
[0051] A mixture of 1.0 kg of dry gel-like composite, 0.5 kg of bastnaesite and 0.47 kg of glycerol aqueous solution (glycerol mass concentration 32%) was kneaded in a kneader for 90 minutes, and then slurry-kneaded in a vacuum slurry kneader for 5 times. The mixture was extruded from an extruder into a honeycomb shape, microwave-dried at 120°C for 30 minutes, and calcined at 750°C for 2 hours to obtain a honeycomb catalyst.
[0052] Example 3
[0053] Under stirring, 0.5 kg of 3-isocyanatepropyltrimethoxysilane was applied to 5.0 kg of sepiolite, and 0.63 kg of tartaric acid was applied to the sepiolite, and the mixture was kept at 70° C. for 60 minutes to obtain tartaric acid-modified sepiolite.
[0054] 1.0 kg of tartaric acid-modified sepiolite was dispersed in 8.0 kg of deionized water, and 0.161 kg of manganese chloride and 0.113 kg of cobalt acetate were added and stirred until completely dissolved. The mixture was heated to 93°C to evaporate water, dried at 125°C for 2 hours, and crushed to obtain a dry gel composite containing CoMn2O4 spinel precursor and sepiolite.
[0055] A mixture of 1.0 kg of dry gel-like composite, 0.8 kg of monazite and 0.44 kg of glycerol aqueous solution (glycerol mass concentration 32%) was kneaded in a kneader for 60 minutes, and then slurry was slurried in a vacuum slurry machine for 6 times. The mixture was extruded from a molding extruder into a honeycomb shape, microwave dried at 105°C for 45 minutes, and calcined at 650°C for 3 hours to obtain a honeycomb catalyst.
[0056] Example 4
[0057] Under stirring, 0.4 kg of 3-isocyanatepropyltriethoxysilane was applied to 5.0 kg of attapulgite, and 0.5 kg of citric acid was applied to the attapulgite, and the mixture was kept at 75° C. for 45 minutes to obtain citric acid-modified attapulgite.
[0058] 1.0 kg of citric acid-modified attapulgite was dispersed in 10.0 kg of deionized water, and 0.239 kg of ferric nitrate and 0.093 kg of copper nitrate were added and stirred until completely dissolved. The mixture was heated to 90°C to evaporate water, dried at 130°C for 1.5 hours, and crushed to obtain a dry gel composite containing a CuFe2O4 spinel precursor and attapulgite.
[0059] The dry gel composite was subjected to XRD and TEM tests. The test results are shown in Figure 2 and Figure 5 Specifically, the XRD test was conducted using a D / max 2500PC X-ray diffractometer from Rigaku Corporation. The test conditions included: Cu K a Radiation, wavelength λ = 1.5406nm, tube current 30mA, tube voltage 40KV. TEM test was carried out using JEM-2100 transmission electron microscope of JEOL Company, Japan. Test conditions include: voltage 200kV. The sample was ultrasonically dispersed in anhydrous ethanol, and after sufficient ultrasonic oscillation, the sample was sucked onto the surface of the copper mesh with a dropper, and tested after drying.
[0060] like Figure 2 It was shown that the dry gel-like composite had diffraction peaks at 2θ of 8.6°, 30.03°, 35.41°, 38.75°, 43.07°, 57.04°, 62.57°, etc.
[0061] For comparison, Figure 3 and Figure 4 The XRD spectra of CuFe2O4 precursor and attapulgite are also given. Figure 3 As shown, the CuFe2O4 precursor has sharp diffraction peaks at 2θ of 30.03°, 35.41°, 38.75°, 43.07°, 57.04°, and 62.57°; and Figure 4 As shown, attapulgite has a diffraction peak at 2θ of 8.6°.
[0062] The diffraction peaks in the XRD spectrum of the dry gel-like composite include the diffraction peaks of the CuFe2O4 precursor and attapulgite, which indicates that the dry gel-like composite contains both the CuFe2O4 precursor and attapulgite.
[0063] from Figure 5 It can be seen that the CuFe2O4 precursor is uniformly loaded on the surface of the fibrous attapulgite clay, rather than agglomerating. The above structure can be attributed to the fact that the citric acid complexing agent is solidified on the surface of the attapulgite, thereby facilitating the in-situ adsorption and deposition of non-precious metal ions on the surface of the attapulgite, and uniformly forming particles of the active ingredient in-situ, avoiding their agglomeration. Figure 5 It is clearly shown that attapulgite and CuFe2O4 spinel precursor are well composited together, that is, the prepared dry gel-like composite is a composite of CuFe2O4 precursor and attapulgite.
[0064] A mixture of 1.0 kg of dry gel-like composite, 1.5 kg of monazite and 0.50 kg of glycerol aqueous solution (glycerol mass concentration 40%) was placed in a kneader for kneading for 50 minutes, and then slurry was slurried in a vacuum slurry machine for 6 times. The mixture was extruded from a molding extruder into a honeycomb shape, microwave-dried at 100°C for 50 minutes, and calcined at 700°C for 3 hours to obtain a honeycomb catalyst.
[0065] Comparative Example 1
[0066] Example 4 was repeated to obtain a honeycomb catalyst, except that the citric acid-modified attapulgite was prepared as follows:
[0067] Under stirring, 0.5 kg of citric acid was applied to 5.0 kg of attapulgite and kept at 75° C. for 45 minutes to obtain citric acid-modified attapulgite.
[0068] As described above, the TEM image of the dry gel composite of Comparative Example 1 was obtained. Figure 6 shown.
[0069] from Figure 6 It can be seen that the CuFe2O4 precursor particles are large and agglomerated, rather than being loaded on the surface of attapulgite clay. Figure 5 and Figure 6 The comparison shows the importance of curing the citric acid complexing agent on the surface of attapulgite through a silane coupling agent.
[0070] Comparative Example 2
[0071] Example 4 was repeated to obtain a honeycomb catalyst, except that the preparation of the dry gel composite was replaced by the following steps:
[0072] 1.0 kg of citric acid-modified attapulgite was dispersed in 10.0 kg of deionized water, and 0.239 kg of ferric nitrate and 0.093 kg of copper nitrate were added and stirred until completely dissolved. The mixture was heated to 90°C to evaporate the water, and dried at 130°C for 1.5 hours to obtain a dry gel composite containing a CuFe2O4 spinel precursor and attapulgite. The dry gel composite was calcined at 700°C for 3 hours and crushed to obtain a composite containing CuFe2O4 spinel and attapulgite.
[0073] Comparative Example 3
[0074] Example 4 was repeated to obtain a honeycomb catalyst, except that monazite was not added.
[0075] Comparative Example 4
[0076] 0.5 kg of citric acid was dissolved in 10.0 kg of deionized water, and 0.239 kg of ferric nitrate and 0.093 kg of copper nitrate were added and stirred until completely dissolved. The mixture was heated to 90°C to evaporate the water, dried at 130°C for 1.5 hours, and crushed to obtain a dry gel composite composed of a CuFe2O4 spinel precursor.
[0077] The XRD test of the dry gel composite showed that Figure 3 In. Figure 3 As shown, the dry gel-like composite has sharp diffraction peaks at 2θ of 30.03°, 35.41°, 38.75°, 43.07°, 57.04°, and 62.57°.
[0078] The dry gel-like composite prepared in all the above steps, 1.5 kg of monazite and 0.5 kg of glycerol aqueous solution (glycerol mass concentration 40%) were placed in a kneader for kneading for 50 minutes, and then slurry was kneaded in a vacuum slurry machine for 6 times. The mixture was extruded from a molding extruder into a honeycomb shape, microwave-dried at 100° C. for 50 minutes, and calcined at 700° C. for 3 hours to obtain a honeycomb catalyst.
[0079] Catalyst performance evaluation
[0080] Catalytic performance: A gas containing p-xylene is used as a VOCs simulation gas, and catalytic oxidation is carried out in the presence of a catalyst sample to test the catalytic performance of the sample. Specifically, the catalyst sample is filled in a VOC adsorption-desorption catalytic reactor. At room temperature, a gas containing p-xylene is generated by bubbling p-xylene solvent with nitrogen. High-purity air is used as a carrier gas to carry the gas containing p-xylene through the VOC adsorption-desorption catalytic reactor. The p-xylene concentration is controlled by adjusting the flow rates of the nitrogen and carrier gas used for bubbling. Specifically, the high-purity air flow rate is 450 mL / min and the nitrogen flow rate is 30 mL / min, so that the p-xylene concentration is 5000 mg / m 3 The concentration of p-xylene at the reactor outlet was analyzed online by a GC-2014 gas chromatograph to calculate the p-xylene conversion rate. Wherein, p-xylene conversion rate (%) = (5000-p-xylene concentration at the outlet (in mg / m 3 )) / 5000. By the temperature (T 99 ) to evaluate the catalytic performance of the catalyst samples. 99 The lower it is, the higher the catalytic performance of the catalyst sample.
[0081] Sulfur resistance: The above catalytic performance test was repeated, except that the p-xylene solvent was replaced by a mixture of p-xylene and dimethyl sulfide in a volume ratio of 9:1. The temperature (T') corresponding to the temperature at which the conversion rate of the mixture was 99% was 99 ) to evaluate the sulfur resistance of the catalyst samples. 99 The lower it is, the higher the sulfur resistance of the catalyst sample.
[0082] Compressive strength: The front and side compressive strength of the catalyst sample were tested according to standard GB / T 5072-2008.
[0083] As described above, the performance of the catalysts of the examples and comparative examples was evaluated. The results are shown in Table 1.
[0084] Table 1
[0085]
Claims
1. A honeycomb catalyst containing spinel-type non-precious metal oxides, which contains (1) fibrous silicate clay, (2) AB2O4 spinel-type oxide, and (3) a rare earth mineral containing lanthanum or cerium, wherein the fibrous silicate clay includes at least one of attapulgite, halloysite, wollastonite or sepiolite, wherein A and B are different non-precious metals and each is selected from at least one of nickel, cobalt, iron, manganese, titanium or copper, and wherein the rare earth mineral containing lanthanum or cerium includes at least one of cerium phosphate, zinc phosphate or bastnaesite.
2. The honeycomb catalyst according to claim 1, wherein the mass ratio of AB2O4 spinel oxide to fibrous silicate clay is 0.08-0.30:1, and the mass ratio of the total amount of AB2O4 spinel oxide, A oxide, B oxide and fibrous silicate clay to the rare earth mineral containing lanthanum or cerium is 0.5-2.0:
1.
3. The honeycomb catalyst according to claim 1, which is basically composed of or consists of the following components: (1) fibrous silicate clay, (2) AB2O4 spinel type oxides, and (3) rare earth minerals containing lanthanum or cerium.
4. A method for preparing the honeycomb catalyst according to any one of claims 1 to 3, comprising the steps of: (1) providing fibrous silicate clay modified with an organic acid; (2) mixing an organic acid-modified fibrous silicate clay, water, a water-soluble salt of A, and a water-soluble salt of B, and drying the mixture to obtain a xerogel-like composite; (3) Mixing the dry gel composite of step (2), the rare earth mineral containing lanthanum or cerium and the extrusion aid, and molding, drying and calcining the mixture to obtain the honeycomb catalyst.
5. The method of claim 4, wherein: Providing the organic acid-modified fibrous silicate clay in step (1) comprises the steps of: applying an isocyanate silane coupling agent and an organic acid to the fibrous silicate clay; Preferably, providing the organic acid-modified fibrous silicate clay comprises the steps of: applying an isocyanate silane coupling agent to the fibrous silicate clay, wherein the mass ratio of the isocyanate silane coupling agent to the fibrous silicate clay is 0.05-0.15:1; and applying an organic acid to the fibrous silicate clay, wherein the mass ratio of the organic acid to the fibrous silicate clay is 0.05-0.2:
1.
6. The method of claim 5, wherein the isocyanate silane coupling agent is at least one of 3-isocyanate propyl trimethoxy silane or 4-isocyanate propyl triethoxy silane, and the organic acid is one of citric acid or tartaric acid.
7. The method of claim 4, wherein: The mixing of organic acid-modified fibrous silicate clay, water, water-soluble salt of A and water-soluble salt of B in step (2) comprises the steps of: dispersing the organic acid-modified fibrous silicate clay in water, wherein the mass ratio of the organic acid-modified fibrous silicate clay to water is 0.05-0.2:1; and adding the water-soluble salt of A and the water-soluble salt of B in such an amount that the mass ratio of AB2O4 spinel oxide to fibrous silicate clay in the obtained honeycomb catalyst is 0.08-0.30:1; Preferably, in step (2), the mixture is evaporated to dryness at 85°C-95°C, dried at 110°C-140°C for 1-3 hours, and crushed to obtain a dry gel composite, wherein the dry gel composite contains AB2O4 spinel oxide precursor and fibrous silicate clay.
8. The method of claim 7, wherein: The water-soluble salt of A is at least one of the nitrate, hydrochloride, sulfate or acetate of A, and the water-soluble salt of B is at least one of the nitrate, hydrochloride, sulfate or acetate of B.
9. The method of claim 4, wherein: The step (3) of mixing the dry gel-like compound, the rare earth mineral containing lanthanum or cerium and the extrusion aid of the step (2) comprises the steps of: kneading the dry gel-like compound, the rare earth mineral containing lanthanum or cerium and the aqueous solution of glycerol for 30-90 minutes, wherein the mass ratio of the dry gel-like compound to the rare earth mineral containing lanthanum or cerium is 0.5-2.0:1 and the mass ratio of glycerol to the dry gel-like compound is 0.05-0.1:1; and performing mud kneading for 4-6 times; Preferably, in step (3), the mixture is formed from an extruder, dried at 90° C.-120° C. for 30-60 minutes and calcined at 550° C.-750° C. for 2-8 hours to obtain the honeycomb catalyst.
10. Use of the honeycomb catalyst according to any one of claims 1 to 3 in degrading volatile organic compounds.
11. The use according to claim 10, wherein the degradation of volatile organic compounds comprises: The honeycomb catalyst is loaded into the reactor, and a gas containing volatile organic matter is introduced into the reactor at a gas space velocity of 4000-25000 h -1 The reaction is carried out at a temperature of 150-550°C to remove volatile organic matter in the gas.
Citation Information
Patent Citations
Spinel type catalyst and preparation method thereof
CN108889301A
Method for preparing Mn-based spinel low-temperature denitration catalyst by complexing acid liquor
CN112337460A
Preparation method of loaded cobalt catalyst
CN106925274A
High-temperature-resistant and wear-resistant nylon composite and preparation method thereof
CN107868453A
Sulfur transfer catalyst and preparation method thereof
CN109465005A